Flexibility in the Parts-of-Speech System of Classical Chinese - Sun, Linlin (Trends in Linguistics. Studies and Monographs [TiLSM], 2020)
Based on empirical data from five classical texts, this study investigates flexibility of parts of speech in Classical Chinese. The findings suggest that flexibility in a parts-of-speech system can only be fully understood by integrating a wide range of aspects. The components needed to account for it include constructions, semantics, metonymies, metaphors, pragmatic implicatures - and world knowledge as reflected within a given culture.